Neutrophil-to-lymphocyte Ratio (NLR) as a predictor for recurrence in patients with stage III melanoma - Ma, Junjie (Sci Rep, 2018)
Neutrophil-to-lymphocyte ratio is a strong predictor for overall survival and disease free survival in many cancers. Our study is the first investigation aiming to determine the predictive value of neutrophil-to-lymphocyte ratio on prognosis of patients with stage III melanoma. This retrospective study utilized a cohort of 107 patients with stage III melanoma treated at Huntsman Cancer Institute, University of Utah, from May 2002 to March 2016. The optimal cutoff of neutrophil-to-lymphocyte ratio was determined by the significance of log-rank tests. A total of 97 log-rank tests were conducted to find the optimal cutoff. Disease free survival was assessed using the Kaplan–Meier method, and univariable and multivariable Cox models were applied to evaluate the predictive value of neutrophil-to-lymphocyte ratio. 2.5 was identified as the optimal cutoff. Kaplan–Meier curve showed that the disease free survival rate of the low value group was significantly higher compared to that of high value group. After adjusting for confounders and other prognostic factors, the neutrophil-to-lymphocyte ratio ≥ 2.5 remained a strong predictor for disease recurrence in patients with stage III melanoma.